2016
DOI: 10.1111/psyp.12671
|View full text |Cite|
|
Sign up to set email alerts
|

Contextualizing individual differences in error monitoring: Links with impulsivity, negative affect, and conscientiousness

Abstract: The error-related negativity (ERN) is a neural measure of error processing that has been implicated as a neurobehavioral trait and has transdiagnostic links with psychopathology. Few studies, however, have contextualized this traitlike component with regard to dimensions of personality that, as intermediate constructs, may aid in contextualizing links with psychopathology. Accordingly, the aim of this study was to examine the interrelationships between error monitoring and dimensions of personality within a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 73 publications
2
27
1
1
Order By: Relevance
“…For example, participants demonstrating post-error speeding may be using a proactive inhibitory strategy, whereas participants demonstrating PES may be using a reactive inhibitory strategy (Buzzell et al, 2018;Cavanagh et al, 2017;Narayanan, Cavanagh, Frank, & Laubach, 2013). Moreover, compensatory mechanisms, effort, anxiety, or depression (see Cavanagh et al, 2017;Gehring et al, 1993;Hill, Samuel, & Foti, 2016;and Olvet, Klein, & Hajcak, 2010 for examples of moderators of error-related brain activity) can also modulate mPFC-lPFC connectivity and may have contributed to the pattern of results in this study.…”
Section: Findings and Contextmentioning
confidence: 87%
“…For example, participants demonstrating post-error speeding may be using a proactive inhibitory strategy, whereas participants demonstrating PES may be using a reactive inhibitory strategy (Buzzell et al, 2018;Cavanagh et al, 2017;Narayanan, Cavanagh, Frank, & Laubach, 2013). Moreover, compensatory mechanisms, effort, anxiety, or depression (see Cavanagh et al, 2017;Gehring et al, 1993;Hill, Samuel, & Foti, 2016;and Olvet, Klein, & Hajcak, 2010 for examples of moderators of error-related brain activity) can also modulate mPFC-lPFC connectivity and may have contributed to the pattern of results in this study.…”
Section: Findings and Contextmentioning
confidence: 87%
“…A total of 106 unique articles was found from searching each database, and an additional 20 articles/datasets were received through contacting labs that routinely examine the internal consistency of ERPs, through examining the references of identified articles, or through social media. Nine articles were excluded for not reporting coefficient alpha estimates for the number of trials used as a cutoff of data inclusion (Cassidy, Robertson, & O'Connell, 2012;Chong & Meyer, 2019;DuPuis et al, 2015;Hill, Samuel, & Foti, 2016;Ip et al, 2018;Lin, 2019;Lin, Stephens, Gavin, & Davies, 2018;Riesel, Richter, Kaufmann, Kathmann, & Endrass, 2015;Segalowitz et al, 2010). Five articles were excluded for having overlapping samples with other studies (Clayson & Miller, 2017a;Larson et al, 2010;Larson, Clayson, & Baldwin, 2014a;Llerena, Wynn, Hajcak, Green, & Horan, 2016;Riesel, Weinberg, Endrass, Meyer, & Hajcak, 2013).…”
Section: Literature Search and Study Selectionmentioning
confidence: 99%
“…While working on a follow‐up project, the authors of Hill, Samuel and Foti () found an error wherein approximately fifty percent of the study data was affected. They have corrected this error, and the corrected results are shared here.…”
Section: Bivariate Correlationsmentioning
confidence: 99%